Is the soft excess in active galactic nuclei real? - Gierlinski, M.; Done, C. (Monthly Notices of the Royal Astronomical Society, 2004)
We systematically analyse all publicly available XMM–Newton spectra of radio-quiet PG quasars. The soft X-ray excess in these objects is well modelled by an additional, cool, Compton scattering region. However, the remarkably constant temperature derived for this component over the whole sample requires a puzzling fine tuning of the parameters. Instead, we propose that the soft excess is an artifact of strong, relativistically smeared, partially ionized absorption. The strong jump in opacity at 0.7 keV from O vii, O viii and iron can lead to an apparent soft excess below this energy, which is trivially constant since it depends on atomic processes. This can have a dramatic effect on the derived spectrum, which has implications for fitting the relativistic smearing of the reflected iron line emission from the disc.
EPrint Processing Status: Full text deposited in DRO
Keywords: Accretion discs; Atomic processes; X-rays; Galaxies.